Marital Bonds And Joint Property Cases: Implications For The Protection Of Spousal Rights - Vicario, Sanchez; Wamafma, Filep; Papare, Meiora Ariella (Mawaddah: Jurnal Hukum Keluarga Islam, 2024)
The main issues raised are how a marital agreement that regulates the separation of property can protect husband and wife's ownership rights over inherited property and how justice is applied in different financial contributions to joint property in civil law. This research aims to explore marital agreements and joint property arrangements and their implications for the protection of husband and wife's rights. This research uses a qualitative method with a normative legal approach to examine the norms of marital engagement and joint property, and their implications for the rights of husband and wife. Data were obtained from regulations, books, documents, and journals, analyzed descriptively to provide a comprehensive picture. The findings show that a marital agreement that regulates the separation of property can provide significant protection to husband and wife's ownership rights over their inherited property, prevent potential conflicts, and ensure better financial management. In addition, fairness in different financial contributions is recognized as important for maintaining balance and harmony in marriage, by recognizing the value of non-financial contributions such as housework and childcare.